Robot‐assisted partial nephrectomy confers excellent long‐term outcomes for the treatment of complex cystic renal tumors: Median follow up of 58 months. (12th September 2016) - Abdel Raheem, Ali; Alatawi, Atalla; Soto, Irela; Kim, Dae Keun; Kim, Lawrence HC; Santok, Glen Denmer; Lum, Trenton GH; Choi, Young Deuk; Rha, Koon Ho
Abstract : Objectives: To analyze long‐term outcomes of robot‐assisted partial nephrectomy for treatment of complex cystic renal tumors. Methods: We retrospectively analyzed the data of patients who underwent robot‐assisted partial nephrectomy for cystic ( n = 32) and solid ( n = 263) renal masses at Severance Hospital, Seoul, Korea. The primary outcome was assessment of perioperative safety for cystic tumor. Secondary outcomes were evaluation of long‐term oncological and functional results. Results: Patients' clinical and demographic characteristics were similar among both groups. The median follow up of cystic and solid masses were 58 and 46 months, respectively. Cystic masses were more likely to have low Fuhrman grade 1 and 2 ( P = 0.03), and shorter operative time ( P = 0.04) compared with solid masses. There was no statistically significant difference regarding warm ischemia time, estimated blood loss, trifecta achievement, length of hospital stay, complication rates and renal function preservation ( P > 0.05) between groups. In the solid group, 12 patients (4.1%) recurred, and six patients (2%) died from metastatic renal cell carcinoma, whereas the patients in the cystic group did not have any local or distance recurrence, and the survival rates were 100%. The 5‐year cancer‐free survival ( P = 0.77), cancer‐specific survival ( P = 0.65) and overall survival ( P = 0.83) rates were similar between the groups. Conclusion: Robot‐assisted partial nephrectomy appears to be safe and feasible treatment for complex cystic renal masses. It confers excellent long‐term oncological outcomes. Robot‐assisted partial nephrectomy should be the treatment of choice for complex cysts whenever feasible.